KOMPLEKSITAS OPERASI PERUSAHAAN DAN TOTAL ASET TERHADAP AUDIT REPORT LAG DENGAN REPUTASI KANTOR AKUNTAN PUBLIK SEBAGAI PEMODERASI - Yenni astika; Meutia, Tuti (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
The aim of this research is to examine the influence of company operational complexity and total assets on audit report lag with the reputation of the public accounting firm (KAP) as a moderating variable in coal mining sector companies listed on the Indonesia Stock Exchange (BEI). The samples in this study were companies obtained from population data of coal mining sector companies listed on the Indonesia Stock Exchange (BEI) for the 2010-2019 period which were selected using the Purposive Sampling method. The data analysis methods used are classic assumption tests such as normality tests, heteroscedasticity tests as well as autocorrelation tests and hypothesis tests such as multiple linear regression tests, T tests, F tests, and R2 tests using SPSS 22 as an analysis tool. The results of the multiple linear regression equation are Y = 7.755 + 0.224X1 + 0.709X2 + e and Y = 7.755 – 0.224X1 + 0.709X2 + 0.122X1X2 + 0.427X1M + 0.431X2M + e. Partially, company operations have a positive and insignificant effect on Audit Report Lag. Total assets have a positive and significant effect on Audit Report Lag. KAP reputation cannot positively and insignificantly moderate the Audit Report Lag. The complexity of company operations and total assets both show a positive and insignificant influence on the Audit Report Lag and the KAP's total assets and reputation have a positive and significant influence on the Audit Report Lag. Suggestions for future researchers are to add other variables in their research. This is because the variables in this study cannot fully explain the condition of Audit Report Lag in more depth in Coal mining sector companies listed on the IDX.